PENGARUH FAKTOR PRODUKSI TERHADAP PENDAPATAN PEMBUDIDAYA IKAN BANDENG DI DESA PANTAI SEDERHANA KECAMATAN MUARA GEMBONG - Nur Apria Putri Pratiwi; Slamet Abadi; Mohamad Sam'un (Universitas Galuh, 2023)
Milkfish production in Bekasi Regency has increased and decreased in recent years, this will affect the income earned by milkfish cultivators. Factors of production can cause an increase and decrease in production. This study aims to analyze the effect of land area, capital, labor, and the amount of output on the income of milkfish cultivators in Pantai Sederhana Village, Muara Gembong District. Research data is sourced from primary data and secondary data. The sample used there are 33 samples. This research is quantitative research with a multiple linear regression method and assisted by Statistical Product and Service Solutions (SPSS) version 25 analysis tool. The variables of this research are the dependent variable (income) and the independent variable (land area, capital, labor, and total production). The results of the study stated that the variable land area did not affect the income of cultivators. The capital variable has a negative effect on income, while the labor variable and the amount of production have a significant positive effect on the income of milkfish cultivators in the Village of Pantai Sederhana, District of Muara Gembong.